A Discussion of a Luxury Apparel Brand Strategy in an Emerging Market: Conceptual Model with Network Perspectives - Rachaya Kaolawanich; Hiroko Oe; Yasuyuki Yamaoka; Chih Yuan Chang (Budapest International Research and Critics University, 2020)
This study explores the Burberry apparel brand’s position and its strategic behaviour seeking new customers in the new market. This exploratory research pays particular attention to business potential and opportunities in an emerging market, Vietnam. To evaluate Burberry’s strategies and the potential, the collaborative network relationships are discussed in details, that is followed by the discussion of the key themes for Burberry to consider in the Vietnamese market, where Burberry has recently begun expanding its businesses. The outcome of the study suggests that the Western luxury brand apparel needs to understand the targeted markets’ systems and consumer behaviour, from there it is inevitable to design strategic plan how to engage the stakeholders in the ubiquitous supply chain relationships. In the end, a conceptual model with network perspectives is proposed: The model will be an analytical framework with key agenda items for the luxury brand which aims to enter the new market, and also the research limitations and further research opportunities are discussed.